Status of Tourism Exports in the Economy - Ruzibaeva, Nargiza Khakimovna (Research Parks Publishers, 2023)
Today, we all know that tourism export is one of the important areas of international services trade. In the economic literature, the high quality of infrastructure and the development of technologies have a positive effect on the development of tourism exports. Taking into account the presence of serious competitors in the world economy and the fact that tourism needs a large amount of investment, the government in each country has to intervene directly and indirectly in this field. In this process, we think that the allocation of tax incentives and subsidies by the state can be more effective. This article discusses exactly such issues.